The alchemy of conquest science, religion, and the secrets of the New World - Bauer, Ralph 1965- (University of Virginia Press, 2019)
"This book explores the role that the verbal, conceptual, and visual language of alchemy played in the literature of the conquest of America and in the rise of an early modern paradigm of discovery in both science and international law. While the roots of the modern 'conquistadorial' attitude toward nature lie in late medieval alchemy, which fused Aristotelian reason with Christian apocalypticism in the militant context of crusade and spiritual conquest, this book argues that the modern idea of what it means to discover something has a colonial history in which conquest legitimated the modern (Baconian) idea of discovery by underwriting it with religious messianism and early modern state power. Thus, the book traces the intellectual and spiritual legacies of such late medieval alchemists as Roger Bacon, Arnald of Villanova, and Ramon Llull in the early modern literature of the conquest of America in texts written by authors such as Christopher Columbus, Amerigo Vespucci, José de Acosta, Nicolás Monardes, Walter Raleigh, Thomas Harriot, Francis Bacon, and Alexander von Humboldt"--
Keywords: Geschichte; Literatur; Nordamerika -- Motiv; Entdeckung -- Motiv; Alchemie -- Motiv; America / Early accounts to 1600 / History and criticism; Alchemy / Early works to 1800 / History and criticism; America / Discovery and exploration; Alchemy; Discoveries in geography; America; Criticism, interpretation, etc; Early works